What we owe (to) the present: Normative and practical challenges for strong longtermism - Lundgren, Björn; Kudlek, Karolina (Futures, 2024)
This paper critically examines the conceptual, normative, and practical challenges to strong longtermism—the view that the far future is the key priority in moral decision-making. The main challenge is that if we take strong longtermism seriously, it follows that harming present and near-future people is permissible, if not obligatory. Given that this conclusion is repugnant to most, we argue that strong longtermism must be substantially weakened. Furthermore, even if strong longtermists bite the bullet on the challenge of what we owe to the present, we raise a set of related concerns that demand attention. Specifically, we argue that it is questionable whether the far future can be a difference-maker in moral decision-making. Even if it could, our inability to predict or understand how the far future will unfold, or what values future generations will hold, severely limits our capacity to account for it. Finally, the implementation of strong longtermism requires a level of progressive moral reasoning that far exceeds our current cognitive and ethical capabilities. While these objections do not necessarily debunk strong longtermism, they seriously challenge its plausibility—as it currently stands.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Future values; Longtermism; Moral change; Moral psychology; Strong longtermism; Uncertainty